Analisis Makna Majas Simbolik Antologi Puisi Nipah Panjang Karya Rini Febriani Hauri - Hakiimu, Hafiizhul; D, Yusra; Akbar, Oky (Universitas Batanghari Jambi, 2024)
This research aims to reveal and strengthen the meaning of symbolic figures of speech in the poetry anthology Nipah Panjang by Rini Febriani Hauri. The type of research used is qualitative research. Data comes from 48 poems in the Nipah Panjang poetry anthology. Data collection techniques use library research and notes. The researcher recorded and marked every word and sentence that contained symbolic figure of speech meaning and then classified it in the data identification table. The results of the research show that the researcher found symbolic meaning from quotes or lines of poetry in the Nipah Panjang poetry anthology and then revealed the meaning of each word from the poetry quote to the meaning of the words. The meaning of the lines of poetry teaches that life is only temporary, death is forever, so always obey the creator. It is hoped that the results of this research can become a reference for reviewing literary works, especially poetry, especially poetry with themes of life, environmental criticism and religion, and can be used as teaching material to review what and how meanings are contained in poetry literary works.